Kajian Hermeneutik Tentang Frasa Tetaplah Kerjakan Keselamatanmu Berdasarkan Filipi 2:12-13 dan Implikasinya Bagi Kekristenan - Angelina Gracesita Zagoto; Robi Panggarra (Anoteros: Jurnal Teologi, 2024)
His study aims to examine the meaning of the phrase "Work Out Your Salvation" based on Philippians 2:12-13 and its implications for Christian life. Utilizing a qualitative research method grounded in hermeneutical principles and a general interpretive approach as outlined by Hasan Sutanto, the study focuses on the text of Philippians 2:12-13. Data were collected through a literature review, with the Bible serving as the primary source, and secondary sources including lexicons, commentaries, theological books, and articles from print and digital media. The findings reveal that the phrase "Work Out Your Salvation" emphasizes the importance of active participation in the process of living out the salvation that has been received. This salvation is not a final destination but an ongoing journey that requires dedication and effort. It involves transformation in mindset and behavior in accordance with the teachings of Christ, as well as engagement in church community life and social service. The implications of this study include the integration of Christian values into daily life and active contribution to community life. The study recommends deeper Bible study, the development of applicable training and educational programs to embody Christ's teachings, and the establishment of supportive church communities for spiritual growth. Penelitian ini bertujuan untuk mengkaji makna frassa “Tetaplah Kerjakan Keselamatanmu” berdasarkan Filipi 2:12-13 dan implikasinya bagi kehidupan kekristenan. Dengan menggunakan metode penelitian kualitatif berbasis prinsip hermeneutik serta pendekatan penafsiran umum menurut Hasan Sutanto, penelitian ini memusatkan perhatian pada teks Filipi 2:12-13. Data dikumpulkan melalui studi kepustakaan, di mana Alkitab digunakan sebagai sumber utama, sementara sumber sekunder mencakup kamu, tafsiran, buku-buku teologi, serta artikel dari media cetak maupun digital. Hasil penelitian mengungkapkan bahwa frasa “Tetaplah Kerjakan Keselamatanmu” menyoroti pentingnya partisipasi aktif dalam prosses menjalani keselamatan yang telah diterima, yang bukan merupakan akhir tetapi sebuah perjalanan berkesinambungan yang membutuhkan dedikasi dan usaha. Hal ini mencakup perubahan pola pikir dan perilaku sesuai dengan ajaran Kristus, serta keterlibatan dalam kehidupam komunitas gereja dan pelayanan sosial. Implikasi dari penelitian ini meliputi nilai-nilai Kristiani dalam kehidupan sehari-hari, serta kontribusi aktif dalam kehidupan komunitas. Penelitian ini merekomendasikan pendalaman dalam studi Alkitab, pengembangan program pelatihan dan pendidikan yang aplikatif untuk penghayatan ajaran Kristus, serta pembentukan komunitas gereja yang mendukung dalam perkembangan spiritual.